2017
DOI: 10.1093/europace/eux218
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, safety, and long-term outcomes of non-powered mechanical sheaths for transvenous lead extraction

Abstract: Using conventional non-powered mechanical sheaths, TLE was effective even in patients at high risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(81 citation statements)
references
References 24 publications
4
64
1
1
Order By: Relevance
“…Furthermore, the authors reported that cardiac tamponade was the most common procedural complication. In multivariate analysis, the total age of the extracted leads was an important factor increasing tamponade risk by about 17% for every 5‐year lead dwell time interval . Kutarski et al reported 95% of complete procedural success and 1.8% of major complications, which is similar to our results.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Furthermore, the authors reported that cardiac tamponade was the most common procedural complication. In multivariate analysis, the total age of the extracted leads was an important factor increasing tamponade risk by about 17% for every 5‐year lead dwell time interval . Kutarski et al reported 95% of complete procedural success and 1.8% of major complications, which is similar to our results.…”
Section: Discussionsupporting
confidence: 90%
“…Kutarski et al in a multivariate analysis identified the total age of extracted leads as a risk factor for major TLE complications. Such a risk increased by about 20% for every 5‐year lead dwell time interval . Furthermore, the authors reported that cardiac tamponade was the most common procedural complication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tendency toward a high frequency of noninfectious indications for TLE in some centers from Poland has previously been noted . In a recent paper, based on data from 2,049 patients, noninfective indications for TLE were observed in 60.2% of patients, which was higher than the incidence reported in previous studies from Europe and the United States (47.3% of the patients in the ELECTRa study and 57.3% of the patients in the data published by the Cleveland Clinic) . We have confirmed that the venous access technique has a strong influence on the electrical function of the leads in the long term.…”
Section: Discussionmentioning
confidence: 98%